Verbal Message and Punctuation Marking in Their Functional Interrelationships - K. Ya. Seagal (Научный диалог)
This study presents a description of the types of functional interrelationships between verbal messages and punctuation marking within the context of individual authorial punctuation practices among Russian speakers from the late 18th to the early 21st century. The research material comprises punctuation and graphic facts predominantly found in literary (both prose and poetry) and scientific texts. The relevance of this study lies in the necessity to represent various types of functional interrelationships between verbal messages and punctuation marking on a unified conceptual basis — namely, informational. It is demonstrated that three such types have emerged in written discourse: verbal message with punctuation marking, verbal message without punctuation marking, and punctuation marking without a verbal message. The differentiation among these types is shown to be conditioned by the varying distribution of primary information conveyed through verbal means and additional information expressed via punctuation markers within written statements. The conclusion drawn indicates that, when semantically interpreting written statements deliberately devoid of punctuation or composed solely of punctuation marks, the implied verbal messages with punctuation marking frequently serve as the background.